Training and Employment of Classic and Semi-Professions: Intensifying versus Accommodating Logics - Jehn, Anthony; Davies, Scott; Walters, David (Canadian Journal of Higher Education, 2022)
Over a half century ago, researchers found that so-called classic professions attract socially advantaged recruits with better labour market outcomes; however, as semi professions become increasingly institutionalized, and classic professional programs expand, differences between these two groups may be less pronounced. Using Statistics Canada’s 2018 National Graduate Survey, we compare inputs and outcomes of four classic professions (law, pharmacy, medicine, and dentistry) and three semi-professions (teaching, social work, and nursing). Bivariate statistics show semi-professions have more non-traditional graduates who invest less in training. Multiple linear regression models also show that after controlling for demographics, classic professions have stronger education-job matches and higher earnings three years after graduation. We interpret these findings as being consistent with our theory of intensifying logic, where classic professions have tight training-job connections, and accommodating logic which suggests semi-professions have looser labour market connections. We end bydiscussing directions for future research on the classic and semi-professions.